ENDOSCOPIC SEPTOPLASTY VERSES STANDARD SEPTOPLASTY IN MANAGEMENT OF DEVIATED NASAL SEPTUM: A RANDOMIZED PROSPECTIVE STUDY - Nayeemuddin, MD; Kumar, Rahul; Kumar, Alok (Student's Journal of Health Research Africa, 2024)
Background One of the common issues that otolaryngologists deal with is nasal obstruction caused by a deviated nasal septum. Many surgical techniques have been tried to treat the same condition. The purpose of the research was to compare the results and risks of endoscopic and standard septoplasty. Methods This research is randomized and potential. The study included 100 individuals with symptomatic deviated nasal septum; 50 of the patients had standard septoplasty, and the remaining patients had endoscopic septoplasty. There was little difference between the two surgeries' functional results. Results In this investigation, intraoperative hemorrhage occurred in 12 patients in the category undergoing standard septoplasty, but only in 4 patients undergoing endoscopic septoplasty. 6 patients undergoing endoscopic septoplasty and 12 patients undergoing standard septoplasty experienced mucosal tears. Synechae development between the inferior turbinate and septum was observed in four patients undergoing standard septoplasty. Conclusion Concerning complications, there was a notable distinction. The results of endoscopic septoplasty were superior in terms of complications. Endoscopic septoplasty makes it simpler to treat detached spurs and posterior deviations. The risks associated with endoscopic septoplasty are lower. Recommendations Based on the findings of this study, it is recommended that endoscopic septoplasty be preferred over standard septoplasty for patients with symptomatic deviated nasal septum due to its lower complication rates and superior postoperative outcomes.